Statins Inhibit Inflammatory Cytokine Production by Macrophages and Acinar-to-Ductal Metaplasia of Pancreatic Cells - Soichiro Ako; Yaroslav Teper; Linda Ye; James Sinnett-Smith; Oscar J. Hines; Enrique Rozengurt; Guido Eibl (Gastro Hep Advances, 2022)
Background and Aims: Animal data show that the presence of an oncogenic Kras mutation in pancreatic acinar cells leads to acinar-to-ductal metaplasia (ADM), pancreatic intraepithelial neoplasia (PanIN), and pancreatic ductal adenocarcinoma (PDAC). Inflammatory macrophages play an important role in the formation of ADMs and transition to PanINs. Epidemiologically, statins are associated with a reduced risk of PDAC. We investigated whether statins inhibit inflammatory cytokine production in macrophages and whether this leads to reduced ADM formation. Methods: The efficacy of statins on inflammatory cytokine production in 2 macrophage cell lines was measured by real-time polymerase chain reaction and enzyme-linked immunosorbent assay. The effect of macrophage-conditioned medium on ADM in primary pancreatic acinar cells was investigated. Mouse pancreatic tissue samples were analyzed for macrophage numbers, cytokine levels, and neoplastic/dysplastic area. Results: Lipophilic statins prevented inflammatory cytokine production in Raw264.7 and J774A.1 cells stimulated by lipopolysaccharide. The inhibitory effect of statins was mediated by inhibition of mevalonate and geranylgeranyl pyrophosphate synthesis and disruption of the actin cytoskeleton but not by a reduction in intracellular cholesterol. Treatment of macrophages with lipophilic statins also blocked ADM formation of primary pancreatic acinar cells. Furthermore, oral administration of simvastatin was associated with a reduction in the number of intrapancreatic macrophages, decreased inflammatory cytokine levels in the pancreas, and attenuated ADM/PanIN formation in mice. Conclusion: Our data support the hypothesis that statins oppose early PDAC development by their effects on macrophages and ADM formation. The inhibitory actions of statins on macrophages may collaborate with direct inhibitory effects on transformed pancreatic epithelial cells, which cumulatively may reduce early PDAC development and progression.